Children's fundamental movement skills: are our children ready to play?. (17th December 2010) - Cowley, Vicki; Hamlin, Michael J; Grimley, Michael; Hargreaves, Jill M; Price, Christopher
Abstract : Children's acquisition of fundamental movement skills is essential for children's participation and success in sport. As part of a larger physical activity study, we assessed 428 (183 baseline, 158 immediately after intervention, 87 after 5 years of intervention) five- to eight-year-old New Zealand children using Ulrich's (1985) Test of Gross Motor Development . This test assessed children's ability to perform the mature pattern of 12 skills: locomotor (run, gallop, hop, leap, horizontal jump, skip and slide), and object control skills (two-handed strike, stationary ball bounce, catch, kick and overarm throw). At baseline, only 4% of the children (4% boys, 5% girls) were able to perform all the locomotor skills in the mature form. The intervention significantly increased the proportion of children able to complete the mature form of these skills to 28% (boys 25%, girls 32%, p < 0.01), which remained relatively high at 31% after 5 years of intervention (22% boys, 40% girls). Similarly, at baseline, only 1% of children were able to complete the mature form of the object control skills. By the end of the intervention, 15% (20% boys, 5% girls) and 5 years later, 13% of children (20% boys, 5% girls) completed the mature form of these skills (p < 0.01). Unfortunately, the proportion of children able to perform the mature form of all skills (locomotor and object control) remains relatively low (1%, 6%, 7%, for baseline, immediately after and 5 years after intervention, respectively) and therefore the focus for teaching and coaching programmes remains the continued improvement of overall skills.